Shaping New Regionalism in the Pacific Islands: Back to the Future? - Satish Chand (Asian Development Bank (ADB), 2010)
The many small sovereign states and multiple shades of sovereignty that exist across the present-day Pacific Island region are largely the product of the region`s colonial history. Yet, the story of regionalism among the Pacific Islands began in pre-colonial times. This history, in turn, has been shaped by the region`s geography and natural resource endowments. The region was colonized after other parts of the world because of its physical isolation and the difficulties of access from Western Europe. Post-colonization, the region was partitioned through contests for space among powers from inside and outside the region, and in response to competition among Protestant and Catholic churches seeking to expand their respective congregations. The security concerns and strategic interests of the major powers have shaped regionalism and are likely to remain important factors for the foreseeable future. Trade integration, however, is not a significant factor contributing to regionalism today. Thus, Pacific Island countries may want to pursue trade liberalization unilaterally.
hdl:11540/1941
Keywords: F13; F15; F59; 330; Pacific Islands; Pacific Island region; regionalism; trade liberalization